Outbreak of Ovine Abortion by Toxoplasmosis in Southeastern Brazil - Gabardo , Michelle de Paula; Oliveira , Juliana Saes Vilaça de; Ecco , Roselene; Guedes, Roberto M. C. (Brazilian Journal of Veterinary Pathology, 2013)
This study describes an outbreak of Toxoplasma gondii abortions in a sheep herd in January/February 2010. An aborted fetus was submitted to the Veterinary Diagnostic Laboratory for post mortem evaluation. Tissue samples were collected and processed by routine histological methods, stained by hematoxylin-eosin and by immunohistochemistry using anti-T. gondii and Neospora caninum specific antibodies. The 250 sheep herd was reared in a semi-intensive production system and one month before delivery the ewes were confined. Forty out of 100 pregnant ewes aborted in the last month of pregnancy or had stillborns. Serum samples previously collected from some ewes were positive for T. gondii by serological test. Histologically, the fetal central nervous system had multifocal necrotic areas surrounded by inﬂammatory cells, with intralesional cysts positive for T. gondii by immunohistochemistry. Based on clinical signs, serology, histopathology and immunohistochemistry results a diagnosis of T. gondii abortion was firmed.